Criminal Responsibility and Challenges in the Criminal Justice System for People with Intellectual Disability in Norway - Erik Søndenaa; Christine Friestad; Birgitte Storvik; Berit Johnsen (Bergen Journal of Criminal Law and Criminal Justice, 2019)
The purpose of this article is to present and discuss Norwegian legislation concerning intellectual disability and criminal responsibility. Current legislation has an internationally unique feature, in that the rules governing criminal responsibility are based on what is known as the medical principle. This implies that criminal responsibility is determined by the defendant’s mental health status at the time of the crime. Norwegian criminal law does not require any causal or correlational relationship between the mental condition and the crime, as do most other jurisdictions. A brief description of historical perspectives and the Norwegian criminal justice system with regard to offenders with intellectual disabilities is also included.